PENGARUH KUALITAS WEBSITE DALAM LAYANAN E-KIOS TERHADAP KEPUASAN MASYARAKAT DI KELURAHAN NGINDEN JANGKUNGAN SURABAYA - Ramadhani, Putu Ayu (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
This research aims to know the effect or relation between website quality and society satisfaction through hypothesis testing research is the website quality in the e-Kiosk service has a positive and significant effect on society satisfaction which formulation of the problem is whether simultaneously and partially the dimensions of variable website quality has a effect on society satisfaction and which of them are the most dominant effect on society satisfaction. The type of this research is correlation research with a quantitative approach through survey method of primary data in the form of a questionnaire. The indicators that used in this measurement is WebQual, include usability (X1), information quality (X2), and service interaction quality (X3) against the society satisfaction (Y) based on expectation satisfaction, experience satisfaction, and overall satisfaction. This research population totaled 7.854 peoples and research sample totaled 100 respondents with accidental sampling method. Based on research results, the regression equation is Y = - 0,474 + 0,089 X1 + 0,437 X2 + 0,012 X3. From the results of the statistical data analysis, indicators that used in this research are valid and reliable. The results of classical assumptions test is free from the problem of multikolonieritas, heteroskedastisitas, and normal distibution. Simultaneously, three variables are effect on society satisfaction. Partially, usability and informational quality has a positive and significant effect on society satisfaction, whereas service interaction quaity is has not a positive and significant effect on society satisfaction. Â  Keywords: Website quality, usability, information quality, service interaction quality, society satisfaction.